Effects of bout duration on players internal and external loads during small-sided games in soccer - Branquinho, Luís Filipe Cardoso (2022)
The evolution observed in soccer over the last years has led to an increase in the physical and metabolic demands required during a game. To prepare players for these demands, coaches must prescribe high-intensity training stimuli, which follow the modern competition's requirements. Thus, selecting the appropriate form, duration, and recovery time of exercises, with the objective of controlling training load, is regarded as a task of vital importance for the enhancement and development of capacities during the training process. Therefore, the general objective of this thesis was to identify which form, duration, and recovery time of a specific training exercise allowed male soccer players to reach and maintain higher training loads. To achieve the proposed objectives, the following sequence of work was conducted: (i) review of the literature on the proposed theme, (ii) comparison between the use of the continuous method or the fractionated method in the training load during the performance of small-sided games, and (iii) assessment of the impact of different recovery times on training load during small-sided games. The main evidence suggests that (i) exercises performed by the fractionated training method induce greater responses at the level of external load when compared to exercises performed by the continuous method; (ii) during the performance of small-sided games, the increase in the number of repetitions of the exercise (fractionated method) induces increases in the external load variables compared to the use of the continuous method; (iii) different recovery times for the same total exercise duration, induced differences in internal and external loads; iv) short recovery periods (i.e. 30 s) were sufficient to maintain high training loads compared to longer recovery periods (i.e. 1-2 min) during the performance of 5-a-side small-sided games v) the fractionated method should be used if the trainer aims to induce high training loads during 5-a-side small-sided games, since the continuous method seems to have caused a decrease in the players physical and physiological responses. This thesis also allows the development of guidelines for the prescription and monitoring of training load in soccer, using small-side games.